Cost Comparison of Microsurgery vs Endovascular Treatment for Ruptured Intracranial Aneurysms: A Propensity-Adjusted Analysis. Issue 3 (23rd September 2022) - Labib, Mohamed A.; Rumalla, Kavelin; Karahalios, Katherine; Srinivasan, Visish M.; Nguyen, Candice L.; Rahmani, Redi; Catapano, Joshua S.; Zabramski, Joseph M.; Lawton, Michael T.
Abstract : BACKGROUND: In specialized neurosurgical centers, open microsurgery is routinely performed for aneurysmal subarachnoid hemorrhage (aSAH). OBJECTIVE: To compare the cost of endovascular vs microsurgical treatment for aSAH at a single quaternary center. METHODS: All patients undergoing aSAH treatment from July 1, 2014, to July 31, 2019, were retrospectively reviewed. Patients were grouped based on primary treatment (microsurgery vs endovascular treatment). The primary outcome was the difference in total cost (including hospital, discharge facility, and all follow-up) using a propensity-adjusted analysis. RESULTS: Of 384 patients treated for an aSAH, 234 (61%) were microsurgically treated and 150 (39%) were endovascularly treated. The mean cost of index hospitalization for these patients was marginally higher ($9504) for endovascularly treated patients ($103 980) than for microsurgically treated patients ($94 476) ( P = .047). For the subset of patients with follow-up data available, the mean total cost was $45 040 higher for endovascularly treated patients ($159 406, n = 59) than that for microsurgically treated patients ($114 366, n = 105) ( P < .001). After propensity scoring (adjusted for age, sex, comorbidities, Glasgow Coma Scale score, Hunt and Hess grade, Fisher grade, aneurysms, and type/size/location), linear regression analysis of patients with follow-up data available revealed that microsurgery was independently associated with healthcare costs that were $37 244 less than endovascular treatment costs ( P < .001). An itemized cost analysis suggested that this discrepancy was due to differences in the rates of aneurysm retreatment and long-term surveillance. CONCLUSION: Microsurgical treatment for aSAH is associated with lower total healthcare costs than endovascular therapy. Aneurysm surveillance after endovascular treatments, retreatment, and device costs warrants attention in future studies.